miRNA‐194 predicts favorable prognosis in gastric cancer and inhibits gastric cancer cell growth by targeting CCND1 - Jingjie Wang; Meixin Zhang; Xinhui Hu; Jiajun She; Ruonan Sun; Shanshan Qin; Dandan Li (FEBS Open Bio, 2021)
MicroRNAs (MiRNAs) play critical roles in regulating target gene expression and multiple cellular processes in human cancer malignant progression. However, the function of miR‐194 in gastric cancer (GC) remains unclear and controversial. In this study, we identified a series of miRNAs that can serve as prognostic biomarkers for GC by analysis of miRNA expression using The Cancer Genome Atlas data. Among them, miR‐100, miR‐125b, miR‐199a, and miR‐194 were the four most promising prognostic biomarkers in GC due to their significant associations with various clinical characteristics of patients. miR‐100, miR‐125b, and miR‐199a predicted poor prognosis in GC, while miR‐194 predicted favorable prognosis in GC. We also provide the first comprehensive transcriptome analysis of miR‐194 in GC. Our data suggest that miR‐194 tends to regulate target genes by binding to their 3′ UTRs in a 7‐mer‐A1, 7‐mer‐m8, or 8‐mer manner. KEGG pathway analysis showed that the cell cycle was one of the pathways most affected by miR‐194 in GC. Moreover, CCND1 was shown to be a novel target gene of miR‐194 in GC. Additionally, downregulation of CCND1 by miR‐194 in GC further led to cell growth inhibition and cell cycle arrest. In conclusion, miR‐100, miR‐125b, miR‐199a, and miR‐194 may have potential as prognostic and diagnostic biomarkers for GC. miR‐194 suppresses GC cell growth mainly through targeting CCND1 and induction of cell cycle arrest.